THE DEVELOPMENT OF PEDAGOGICAL THOUGHT IN THE BUKHARA KHANATE IN THE 16TH-17TH CENTURIES (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This article analyzes that by the 16th and 17th centuries, Central Asia was a period of many conflicts and disputes, the crisis of feudalism, the moral decay of feudal rulers, the growing looting of the people, the growing protests of ordinary working people against oppression.